Clinical Profile of Patients Diagnosed with Liver Abscess – a Retrospective Study at a Teaching Hospital - Goswami, Brijesh; Makwana, Harsha; Nanda, Vivek (Clinical and Research Journal in Internal Medicine, 2024)
Background: Liver abscesses continue to present a significant diagnostic and therapeutic challenge to the medical community. Early clinical distinction between an amoebic and a pyogenic liver abscess is challenging due to their overlapping clinical presentations. Aim: The present study was undertaken to evaluate the clinical characteristics, lab parameters as well as management in patients suspected of liver abscess. Methods: A retrospective study was carried out in 60 consecutive patients presenting with liver abscess, admitted at tertiary care hospital. Lab investigations were carried out. All patients underwent ultrasound-guided aspiration of a liver abscess either by percutaneous needle or by a pigtail catheter.  Patients were monitored during the period of hospital stay to note their outcome. The data variables collected were compiled by using an excel spreadsheet and later analysed using Medcalc (version 20.118). Results: The commonly observed clinical presentation was abdominal pain (95%) followed by fever (57%) and jaundice (7%). On examination, 60% of the liver abscess cases had right hypochondrial tenderness while Hepatomegaly was observed in about 17% of the subjects. Leucocytosis was observed in 67% of the cases in view of underlying infectious etiology. The size of the majority (60%) of the liver abscess were in the range of 5.1 to 9.9 cms and right lobe was the most affected region (75.2%). Conclusion: Early recognition of symptoms, institution of antibiotic and amoebicidal therapy and drainage of abscess via appropriate modality improves the prognosis of liver abscess.